Diversity and Distribution of Traditional Home Gardens Along Different Disturbances in a Dry Tropical Region, India - Patel, Sanoj Kumar; Sharma, Anil; Singh, Rinku; Tiwari, Amit Kumar; Singh, Gopal Shankar (Frontiers in Forests and Global Change, 2022)
Home gardening is an indigenous practice of cultivation that has effectively adapted to local ecological conditions over generations. This study examined the effects of disturbance and garden size on biodiversity to develop a better understanding of vegetation cover and its role in livelihood and provision of forest management in the Vindhyan highlands. Data were collected from 60 gardens which were classified into large (> 650 m2), medium (400–650 m2), and small (< 400 m2), based on size and disturbance gradients viz., high, medium, and low. A total of 133 species from 50 families were recorded, in which trees (47.4%) were dominant followed by shrubs (18%) and herbs (16.5%). With respect to disturbance, the highest number of tree species (39) were found at low disturbance (LD) followed by 33 species in medium disturbance (MD) and 32 species in high disturbhance (HD). The total mean richness of species was greater at LD (20.3 ± 2.3) and lowest at HD (18.5 ± 2.2). Tree density was significantly (P ≤ 0.05) higher at LD (293.75 ± 16.1 individual ha–1) as compared to MD (221 ± 11.5 individual ha–1) and HD (210 ± 10.3 individual ha–1). However, the results for shrubs and herbs density were considerably different, where shrubs density was highest at HD (70 ± 6.9 individual per 1,000 m2) and lowest at LD (62.5 ± 5.8 individual per 1,000 m2), while the maximum density of herbs was recorded at MD (466.25 ± 29.8 individual per 100 m2) and minimum at LD (370 ± 21.4 individual per 100 m2). The summed dominance ratio indicated frequent use of garden plants in bio-fencing, vegetables, ornamental, and ethnomedicine. Diversity (P < 0.01) and species richness (P < 0.05) showed a significant positive correlation with garden size. The Principal Component Analysis (PCA) showed that the first component (PC1) accounted for 28.6% of variance, whereas the second explained 21.9% of variance in both disturbance and garden size with a cumulative variance of 50.5%. These components depicted the positive association with HD (14.34), SDiv (13.91), TCD (12.47), and HDiv (12.09). We concluded that the diversity of home gardens changed with disturbance, which crucially served as a refuge for native tree species in a degraded landscape. This pattern highlighted the importance of home gardens for plant biodiversity conservation and local livelihood, which must be a viable option for regeneration of deforested dry tropics, while also reducing the burden on dry tropical forest regions.